Linear Motors Utilization for Oth Maglev and Railway Vehicles - Binder, A.; Werle, Th. (Communications - Scientific letters of the University of Zilina, 2001)
Traction Systems with Linear Machines have been under investigation for a long time. There were and are several applications with synchronous long stator linear machines, e.g. the maglev demonstration line in Berlin MAGNETBAHN (built in 1983), the high speed maglev line TRANSRAPID where the TR06 has been tested since 1984 or the YAMANASHI Test Line in Japan, built in 1990. The linear – motor technology cannot only be used for propulsion of new linear trains. When thinking of adhesion problems of conventional locomotives under wet weather conditions, it is also possible to use the magnetic attraction force produced by linear machines to increase the adhesion – based tractive effort between wheel and rail.